2005
DOI: 10.1103/physrevlett.95.263002
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Photodetachment in a Strong Laser Field of Circular Polarization

Abstract: Negative fluorine ions are exposed to a circularly polarized infrared laser pulse with a peak intensity on the order of 2.6 x 10(13) W/cm(2). A fundamental difference, as compared to the case of linearly polarized field, is found in the absence of any structure in the photoelectron spectrum that can be associated with the quantum interference effect. This observation is in accord with our recent predictions [S. Beiser, Phys. Rev. A 70, 011402 (2004)10.1103/Phys. Rev. A.70. 011402]. The experiment reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 17 publications
0
47
1
3
Order By: Relevance
“…1 has support from other considerations. The momentum distribution for photoelectrons from ionization with circular polarization as given in the work of Bergues et al [14] is shown here in Fig. 5.…”
Section: Referencesmentioning
confidence: 97%
See 1 more Smart Citation
“…1 has support from other considerations. The momentum distribution for photoelectrons from ionization with circular polarization as given in the work of Bergues et al [14] is shown here in Fig. 5.…”
Section: Referencesmentioning
confidence: 97%
“…5. (Color online) A momentum distribution measured by the Freiburg group [14] clearly shows the circular motion of a photoelectron produced by a circularly polarized laser beam. The propagation direction of the beam lies along the vertically oriented axis in the figure.…”
Section: Role Of the Ponderomotive Potentialmentioning
confidence: 99%
“…Negative ions are particularly amenable to investigation by methods based on the strong-field approximation (SFA) [55], since their neutral core dictates that the detachment dynamics is influenced by short-range interactions alone. Investigations on the response of negative ions to circularly-polarized fields are becoming more prevalent [52,57,58]. Additionally, recent SFA calculations of photoelectron momentum distributions for F − , subject to orthogonal laser fields, have shown good agreement with those obtained by solving the time-dependent Schrödinger equation within the SAE approximation [59].…”
Section: Introductionmentioning
confidence: 98%
“…The bracket symbol that appears in Eqs. (28) and (29) is the ceiling function, meaning the smallest integer containing the quantity within the bracket. Each circularly polarized photon possesses one quantum unit of angular momentum, and all of these angular momenta are aligned, meaning that the photoelectron should possess about 17 quantum units of angular momentum.…”
Section: B Circular Polarization In the Lgmentioning
confidence: 99%